A New Record of Microarthridion littorale (Copepoda, Harpacticoida, Tachidiidae) from Korea with Taxonomic Note on the Species - Jong Guk Kim; Hyun Ki Choi; Seong Myeong Yoon (Animal Systematics, Evolution and Diversity, 2016)
A harpacticoid copepod, Microarthridion littorale (Poppe, 1881), is newly recorded in Korea. Microarthridion species can be distinguished from each other by a combination of the number of the antennular segment, the number of the seta on the antennary exopod, and the armature of the thoracopod legs. Korean materials examined coincide well with M. littorale on these well-known characteristics. However, there are some minor differences in the ornamentations of the maxilliped and swimming legs. The specimens show additional sexual dimorphisms in the setae on enp-3 of P1 and exp-3 of P2-P4. Morphological diversity of so-called M. littorale is also discussed here with detailed features.